A LITERATURE REVIEW: THE POTENTIAL OF NATURAL INGREDIENTS AS ANTIDEPRESSANTS - Ranatri Puruhita; Arifah Sri Wahyuni; Andi Suhendi (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
Changes in mood, physical well-being, and behavior, such as sleep and hunger patterns, psychomotor abilities, concentration, anhedonia, exhaustion, hopelessness, helplessness, and suicidal thoughts, define a mental illness known as depression. Alternative therapies that can be used to avoid these side effects include herbal medicines from several types of plants. This literature review aims to determine the potential of natural ingredients that have antidepressant activity in plant biomarkers, methods of obtaining biomarkers, effective dose, and their mechanisms of action. Article searches use keywords ("Herbal plant" OR "Medicinal plant" OR "Herbal" OR "Plant Extract" OR "Plant Extracts") AND ("Antidepressant" OR "Antidepressive") AND ("Mechanism of antidepressant") using the Science Direct, PubMed, and Google Scholar databases. The final results included eight research articles in the systematic review that met the inclusion criteria. Plants that have antidepressant potential include flowers of Viola odorata L, Crocus sativus, Impatiens glandulifera, and Leptadenia hastata (Pers.) and Alpinia zerumbet, seeds of Nigella sativa, root of Panax ginseng, and Achyranthes aspera. Keywords: Antidepressants, Natural Ingredients, Literature Review